DEVELOPMENT OF PHYSICAL TRAINING AND SPORTS IN THE REPUBLIC OF UZBEKISTAN - Abdukakhorov Ulugbek Abduganievich; Ismoilov Ravshanjon Bakhriddinovich; Abdulxakimov Zuhrali Tursunalievich; Bakhriddinov Jahongir Ravshanjon ogli (International Engineering Journal For Research & Development, 2020)
This article provides information on the ways of rapid development of physical culture and sports in the Republic of Uzbekistan, its existing problems, future directions of development.